KONSEPSI Al-GHAZALI TENTANG FIQH DAN TASAWUF - Deswita, Deswita (JURIS (Jurnal Ilmiah Syariah), 2014)
Al-Ghazali was a sufism and a “faqih”. He was a smart and intelligent one. He knew of how to combine the ability of “fiqh” and sufism. In combining the two knowledges, he usually saw the internal aspects between the two eventhough they were different focus of study, but they were could not be separated each other. He thought that sufism gave something important to ‘Fiqh” because they sould standed together.